A 'bioproduction breadboard': programming, assembling, and actuating cellular networks. (December 2015) - Zargar, Amin; Payne, Gregory F; Bentley, William E
Graphical abstract: Highlights: Pathway engineering approaches create opportunities for new products and processes. Cell populations are assembled independently, but linked for desired functionality. Signaling modalities, such as light and metabolite level, offer dynamic control. Genetic switches are linked with signaling modalities for actuation. Perspectives for future linkage suggest 'bioproduction breadboard'. Abstract : With advances in synthetic biology and biofabrication, cellular networks can be functionalized and connected with unprecedented sophistication. We describe a platform for the creation of a 'bioproduction breadboard'. This would consist of physically isolated product-producing cell populations, product capture devices, and other unit operations that function as programmed in place, using unique, orthogonal inputs. For product synthesis, customized cell populations would be connected through standardized, generic inputs allowing 'plug and play' functionality and primary, user-mediated regulation. In addition, through autonomous pathway redirection and balancing, the cells themselves would provide secondary, self-directed regulation to optimize bioproduction. By leveraging specialization and division of labor, we envision diverse cell populations linked to create new pathway designs.